Implementasi Sistem Informasi Akuntansi pada Usaha Mikro Kecil Menengah (UMKM) Bidang Pendidikan di Sumatera Barat (Studi Empiris pada Lembaga Bimbingan Belajar di Sumatera Barat) - Sri Wahyuni Riza; Dwila Maresti (Universitas Batanghari Jambi, 2020)
Technological developments directly drive the need for information, including the need for financial and accounting information for an entity or institution. Not only large entities or institutions, but the need for financial and accounting information from micro and small businesses has become important. One of the small and medium micro businesses that also have to meet the needs of financial and accounting information for external parties is a tutoring institution. Previous research has reviewed a lot about the development of accounting information systems and their application to micro, small and medium enterprises. The purpose of this study is to conduct an empirical study of the implementation of accounting information systems in micro small and medium enterprises of tutoring institutions in West Sumatra. This research is quantitative research. The data obtained is primary data through the distribution of online quizzes through Google Drive to tutoring institutions in West Sumatra. The result is that in micro businesses, especially tutoring institutions in West Sumatra are still minimal in the use of accounting information systems in managing business finances.